La enseñanza de inglés con propósitos profesionales para la carrera de contador público: una experiencia en la FCE- Universidad Nacional de Río Cuarto - Picchio, Romina; Dichiara, Anabella (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This pedagogical proposal describes an experience of teaching English for specific purposes (ESP) at the National University of Río Cuarto, in which curricular modifications were implemented based on a change in the curriculum for Public Accounting, at the Faculty of Economic Sciences of this university. This article describes the needs analysis process that was carried out to adjust the proposal to the context of the new curriculum design. At the same time, the objectives and contents of the renewed version of the course are detailed, as well as its teaching and assessment methodology. Finally, the opinions of the group of students who participated in the course in 2023 are summarized, presenting some conclusions and projections from this first teaching experience.